Level of Knowledge about Medical Emergency Management by Fifth- and Sixth-Year Students from the School of Dentistry at the Universidad Autónoma del Paraguay Pierre Fauchard (Revista Nacional de Odontología, 2017)
Introduction: Medical emergencies are events that have immediate consequences and are life threatening,for which they require fast and accurate action. Aim: To determine the level of knowledge of fifth- and sixth-year students from the School of Dentistry at theUniversidad Autónoma del Paraguay Pierre Fauchard on the management of medical emergencies that mayarise during consultation. Materials and methods: Cross-sectional, descriptive, observational study. A survey was conducted to testtheir knowledge about medical emergencies through a structured questionnaire, with 25 multiple choiceclosed-ended questions to measure the established variables. The sample consisted of 146 fifth- and sixth-year students. The variables of interest were age, sex, participation in first aid courses (theoretical or theo-retical-practical) and level of favorable or unfavorable knowledge, based on a 60 % scale in which a total of15 correct answers is considered favorable. Results and conclusions: It is concluded that the level of knowledge of fifth- and sixth-year students fromthe School of Dentistry at Pierre Fauchard was unfavorable in 56 %, in a predominantly female populationwith a percentage of 87.7 %, and an age group of 23 years old with a percentage of 35.6 %. Only 17.8%of the students participated in a first aid course, of which 6.8 % was theoretical and 11.0 % was theoreti-cal-practical.
Keywords: students; knowledge; emergency; dentistry